Effect of mild or moderate hepatic impairment on the pharmacokinetics of risdiplam. Issue 8 (1st April 2022) - Kletzl, Heidemarie; Ajmi, Hassan; Antys, Izabela; Heinig, Katja; Jaber, Birgit; Marbury, Thomas C.; Young, Annie; Günther, Andreas
Abstract : Aim: This phase I, multicentre, open‐label, nonrandomised, parallel‐group, two‐part study aimed to evaluate the effect of mild to moderate hepatic impairment on the pharmacokinetics (PK), safety and tolerability of a single oral dose of risdiplam. Methods: Adult subjects (aged 18‐70 years) with mild (Child‐Pugh Class A; Part 1) or moderate (Child‐Pugh Class B; Part 2) hepatic impairment were matched with subjects with normal hepatic function on sex, age, body mass index and smoking status. Each subject received a single oral dose of 5 mg of risdiplam. Plasma concentrations of risdiplam and its metabolite M1 were measured and PK parameters were compared. Adverse events, laboratory abnormalities, vital signs and electrocardiogram measurements were assessed. Results: After a single dose (5 mg) of risdiplam, the risdiplam PK parameters area under the plasma concentration‐time curve from time zero to infinity and maximum observed plasma concentration were approximately 20% and 5% lower, respectively, in subjects with mild hepatic impairment and approximately 8% and 20% higher, respectively, in subjects with moderate hepatic impairment compared with subjects with normal hepatic function. These differences were not statistically significant; all 90% confidence intervals for geometric least squares‐means ratios spanned unity. No new risdiplam‐related safety findings were observed in subjects with mild or moderate hepatic impairment. Conclusion: Mild or moderate hepatic impairment did not have a clinically relevant impact on the PK of risdiplam. Therefore, no dose adjustment is required in patients with mild or moderate hepatic impairment when receiving risdiplam. Abstract :